Исследование парамагнетных свойств углеродосодержащих низкоразмерных веществ - Г. Шилагарди; Ж. Ванчинхүү; С. Мөнхцэцэг (Scientific transaction of the National University of Mongolia. Physics, 2022)
The results of the study of petrified lignine and charcoals by the method EPR have been presented. The study has been showed that the concentration of paramagnetic center connected with the organic mass of petrified lignine is more than the concetration of bituminous coals from medium degree metamorphism. Consequently, the calorific ability of petrified lignine can be proved to be greater than the calorific ability of the bituminous coals. Futhermore, we have revealed that paramagnetic centers are presented in charcoals so is in petrified lignine.